The ichnogenus Dictyodora from late Silurian deposits of central-western Argentina: Ichnotaxonomy, ethology and ichnostratigrapical perspectives from Gondwana - Pazos, Pablo Jose (2015)
The association of trace fossils from the Late Silurian Río Seco de los Castaños Formation in central-western Argentina (San Rafael Block) is mainly composed of Dictyodora, including Dictyodora scotica, Dictyodora tenuis and a new ichnospecies named Dictyodora atuelica. The latter shows a tendency to migrate to a deeper level - analogous to Dictyodora liebeana's - which reflects more sophisticated behavioural patterns. The Dictyodora ichnospecies (one of the most diverse assemblages in Gondwana) coexists with Nereites. SEM observations and EDS analyses suggest that the wall structure of Dictyodora could be the result of an activity other than the traditional suggestion of respiration, e.g., feeding. The succession, including some of the levels containing Dictyodora, presents microbially induced sedimentary structures (MISS) that would indicate a photic zone. This discovery favours previous deltaic interpretations instead of the deep-sea fan deposits traditionally suggested for the Siluro-Devonian greywackes of the Cuyania terrane, and particularly for this unit. The abundant Dictyodora, Nereites, Zoophycos and undermat miners ichnofossils, as well as the scarce arthropod trackways, resemble older records in Europe and North America. The studied section is very well age-constrained, and the autochthonous Gondwana ichnofauna permits to cast doubt on previous interpretations, suggesting that after the Ordovician, microbial mats retreated to marginal marine environments and then spread later in the Carboniferous. More importantly, the occurrence of Dictyodora and Nereites in beds that bear abundant wrinkle structures or records of biofilms in some places is challenging with regard to deep-sea interpretations. Dictyodora is probably not a good stratigraphic indicator, and the provincialism suggested for this ichnogenus may be an artefact of the lack of more complete records in Gondwana.